Cochlear deformities and its implication in cochlear implantation: a review - Swain, Santosh Kumar (International Journal of Research in Medical Sciences, 2022)
Hearing loss is one of the world’s leading causes of chronic health conditions. Cochlea plays a vital role in the hearing mechanisms and it converts sound energy into electrical stimuli which are transmitted to the brain through the neural pathway. The human cochlea is difficult to explore because of its vulnerability and bordering bony capsule. Congenital malformation of the inner ear or cochlea is an important cause of congenital sensorineural hearing loss. The deformity of the cochlea may result from arrested development of cochlea at different stages of fetal life or from abnormal development due to genetic abnormalities. There are hair cells responsible for converting sound energy into electrical impulses. These hair cells are easily damaged, which results in permanent hearing loss. Cochlear implants are surgically implantable biomedical devices that bypass the sensory hair cells and directly stimulate the remaining fibers of the auditory nerve with an electric current. Cochlear implantation is capable of restoring a surprisingly large degree of auditory perception to patient that is suffering from severe to profoundly deaf. Children with cochlear anomalies are thought to have poorer outcomes with cochlear implantations, therefore would be poorer candidates due to their diminished ability to interpolate and use auditory information provided through a cochlear implant. Parents should be counselled to establish realistic post-implant expectations in case of children with cochlear deformity. So, patient selection has emerged as one of the most vital determinants of successful outcomes after pediatric cochlear implantation.